How to Teach Phonology in the Classroom (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
English phonology is one of the biggest part of this language and teaching this to the student can require responsibility of being aware of every sound. Phonology in language teaching refers to the study of sound patterns within a language and across languages. Specifically, it focuses on the categorical organization of speech sounds, known as phonemes, in the mind and how these sounds convey meaning. Unlike phonetics, which examines the physical production and perception of sounds, phonology delves into the distinctive sound units that shape language. In language classrooms, phonological areas include intonation, stress, accent, and features of connected speech (such as elision, intrusion, and catenation)  Essentially, phonology helps teachers understand and teach the unique sound system of a language, enabling effective pronunciation instruction.